1975
DOI: 10.1097/00000658-197505000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy as an Adjuvant to Surgery for Colorectal Cancer

Abstract: A combined intraoperative and postoperative adjuvant program of 5 minus Fluorouracil (5 FU) for patients undergoing "curative" resection for adenocarcinoma of the colon and rectum was initiated as a randomized clinical trial in January 1968. Patients at the Medical College of Virginia and the University of Virginia were randomly assigned to an intraluminal 5 FU or intraluminal control (Saline) group and were so treated at the time of surgical resection if findings at operation indicated that all gross neoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1976
1976
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(7 citation statements)
references
References 4 publications
1
5
0
1
Order By: Relevance
“…Moreover, the prognostic outcomes for patients with advanced CRC is poor [ 2 ]. 5-fluorouracil (5-Fu), which acts by interfering with cellular DNA synthesis and histone deacetylation, is recommended as a first-line chemotherapeutic option for CRC [ 3 , 4 ]. Clinically, administration of 5-Fu combined with irinotecan or oxaliplatin is considered to be a relatively standard chemotherapeutic regimen [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the prognostic outcomes for patients with advanced CRC is poor [ 2 ]. 5-fluorouracil (5-Fu), which acts by interfering with cellular DNA synthesis and histone deacetylation, is recommended as a first-line chemotherapeutic option for CRC [ 3 , 4 ]. Clinically, administration of 5-Fu combined with irinotecan or oxaliplatin is considered to be a relatively standard chemotherapeutic regimen [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These strategies are multidirectional and composed of surgery, radiation therapy, chemotherapy, and targeted therapy (Damin & Lazzaron, 2014). Among them, chemotherapy utilizes different drugs or combinations of them and is administrated as an adjuvant after surgery (Goyle & Maraveyas, 2005; Lawrence et al 1978). Almost half of the CRC patients might develop recurrence due to surgical resection and aggressive chemotherapy, which underscore the necessity of improving novel therapies (de la Cueva et al, 2013; González‐Vallinas et al, 2013; Rangwala et al, 2012; P. R. Subbarayan et al, 2010; Wehler et al, 2013).…”
Section: Inhibition Of the Pi3k/akt/mtor Pathway In Crc Either As Mon...mentioning
confidence: 99%
“…Three trials have suggested that 5-fluorouracil is of value (Li & Ross 1976, Mackman et al 1974, Mavligit et al 1976, but all have relied on historical controls. The two studies showing no benefit (Grage et al 1975, Lawrence et al 1975 were, however, prospective randomized series. The value of 5-fluorouracil as an adjuvant in rectal cancer is doubtful, and it has been argued that the next step, which is already being taken in America, should be trials using a combination of drugs.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%